Pelaksanaan Rencana Pulang H-1 pada Pasien Rawat Inap di RSUP Dr Kariadi Semarang - Wahyu Wiryawan; Chriswardani Suryawati; Dodik Tugasworo Pramukarso (Jurnal Manajemen Kesehatan Indonesia, 2022)
Discharge planning is an important and crucial process in patient’s service transition. Well planned discharge planning will increase patient’s flow. At Dr Kariadi Central General Hospital, according to the evaluation of the patient's discharge in September 2021, it was found that only 13% of patients had planned discharges. A qualitative study was conducted from January to March 2022. This study aims to know the implementation of the day before discharge program at Dr. Kariadi Central General Hospital. The subject was patient from 1st and 2nd class inpatient installation and 3rd class inpatient unit - stroke unit of Dr. Kariadi Central General Hospital Semarang. Data were obtained from in-depth interviews with all elements involved in planning the day before discharge, observation, and document review. Based on the result of our study, implementation of one day before discharge plan at Dr. Kariadi Central General Hospital Semarang has been unconsistantly increased (to 77,73% on February 2022, 76,45% on march 2022, and 77,69% on April 2022), even though it has not achieved the expected goal yet (more or equal to 80%), several factors influenced the implementation of patient discharge process, such as regulations, doctors and assistants (regarding doctor’s visite schedule), patient and family, and communication between doctor, nurse, other medical staff, and patient. Our study concluded that one day before discharge plan at Dr. Kariadi Central General Hospital Semarang  can be improved.